Toxicity evaluation of leached of sugarcane vinasse: Histopathology and immunostaining of cellular stress protein - Coelho, Maria Paula Mancini [UNESP]; Correia, Jorge Evangelista [UNESP]; Vasques, Louise Idalgo [UNESP]; Marcato, Ana Claudia de Castro [UNESP]; Guedes, Thays de Andrade [UNESP]; Soto, Miguel Alfaro [UNESP]; Basso, Juliana Broggio [UNESP]; Kiang, Chang [UNESP]; Fontanetti, Carmem Silvia [UNESP] (Elsevier, 2018)
Sugarcane vinasse is a residue generated at a rate fifteen times greater than the ethanol production. Because of its high organic and micronutrient content, this residue is used as a fertilizer on sugarcane crops. However, when used in large quantities, vinasse can saturate the soil and contaminate nearby water resources by percolation and leaching. Given the proven toxic potential of in natura vinasse, the present study aimed to evaluate the toxic potential of leached sugarcane vinasse using Nile tilapia (Oreochromis niloticus) as a test organism. A bioassay was performed after vinasse percolation in laboratory soil columns. The bioassay included one control group containing fresh water and two treatment groups, the first exposed to a 2,5% dilution of leached of vinasse and the second to a 2,5% dilution of in natura vinasse. After exposure, histopathological analysis was performed in gills and livers, and the latter were labelled for HSP70 proteins. No significant changes were detected in the gills of the exposed fish. However, in the liver, both in natura and leached vinasse induced statistically significant histopathological changes. These changes include hydropic degeneration, cell boundary losses, pyknotic nuclei and cellular disorganization. HSP70 expression significant increase in liver of both treatment groups were observed, being higher for the in natura vinasse exposed group. Results suggested that both leached vinasse and in natura vinasse were toxic, its still able to provoke histological changes and induce the cytoprotective response in exposed fish liver, evidenced by a immunostaining of cellular stress proteins. Thus, in order to reduce its environmental impact, appropriated effluent disposal is essential.
Keywords: Aquatic toxicity; Gill; Histology; Immunohistochemical; Liver